Knowledge management toolkit : practical techniques for building a knowledge management system - Tiwana, Amrit (Prentice Hall PTR Upper saddle RiverUS, 2000)
Provides a 10-step guide for implementing a knowledge management (KM) strategy and a KM system in 4 phases, namely: infrastructural evaluation; KM system analysis, design and development; system deployment; and, evaluation. Seeks to provide practical guidance for linking knowledge management to business strategy in areas including building on the company's existing intratranet, data warehouse, and project management investments. Includes checklists, KM case studies and a CD-ROM.